Maternal and perinatal outcome of teenage pregnancy in a tertiary care centre - Subedi, Anjali; Shrestha, Junu; Shrestha, Aashika; Gurung, Sangeeta (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To evaluate the maternal and perinatal outcome in adolescent pregnancy, Method: This was a cross-sectional study conducted in Department of Obstetrics and Gynecology, Manipal Teaching Hospital, Pokhara from October 2017 to March 2018 for duration of 6 months. Results: There were total 82 cases of teenage pregnancy in the study duration with incidence of 6% among total deliveries. Majority of cases were of age 19 and were primigravida. Fifty five percent of the cases had normal vaginal delivery and cesarean section accounted for 39% of cases. The major indication for cesarean section was meconium stained liquor (52%) followed by oligohydraminos (15%) and cephalopelvic disproportion (11%). The maternal complication accounted for 59% of total cases. Among them, anaemia was highly prevalent comprising 11% of cases followed by PPROM (9.8%) and hypertensive disorders in pregnancy (8.5%). In perinatal outcome, the incidence of preterm birth was 15.9% and low birth weight was 13.4%. The rate of NICU admission was 2.4% and there was one case of still birth. Conclusion: The study showed that teenage pregnancy is at increased risk of adverse maternal and perinatal outcome. So if we lay an effort for reducing the incidence of teenage pregnancy, we can bring in positive changes in the indicators of maternal and perinatal morbidities.